2019
DOI: 10.3126/jcmc.v9i2.24535
|View full text |Cite
|
Sign up to set email alerts
|

Assertiveness and Self-Esteem among Nursing Students of Manipal College of Medical Science of Pokhara, Nepal

Abstract: Background: Assertive behaviour and low self-esteem have been found to major problem in the nursing profession. Nursing students today are the backbone of professional nurses of tomorrow. In order to ensure competent and safe practice, it is necessary for them to be individuals with high assertive skills and self-esteem. This study was conducted to identify assertiveness and self-esteem among nursing students. Methods: A descriptive cross sectional survey was conducted among 202 Proficiency Certificate L… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 4 publications
2
6
0
Order By: Relevance
“…They may be able to perform tasks on par with the majority of people, possess a variety of positive traits and skills, have a high level of artistic skill perception, have a positive outlook on life, and believe they are at least on par with other people in terms of value. The results of the present study are in agreement with those of Shrestha (2019) [ 32 ] and Nandan (2021), [ 33 ] who found that the majority of nursing students exhibit moderate assertiveness and self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…They may be able to perform tasks on par with the majority of people, possess a variety of positive traits and skills, have a high level of artistic skill perception, have a positive outlook on life, and believe they are at least on par with other people in terms of value. The results of the present study are in agreement with those of Shrestha (2019) [ 32 ] and Nandan (2021), [ 33 ] who found that the majority of nursing students exhibit moderate assertiveness and self-esteem.…”
Section: Discussionsupporting
confidence: 93%
“…Studies among Japanese and Indian nurses found that nurses' self-esteem improved after assertiveness training (Kanade, 2018;Shimizu et al, 2004). Similarly, a significant positive correlation between assertive behavior and self-esteem was reported in a study conducted in India among nurses (Binuja, 2020;Maheshwari & Gill, 2015) and in Nepal among nursing students (Shrestha, 2019). This study proposes that efforts should be made to improve and to achieve healthy and balanced self-esteem among nurses to better communicate and assert themselves in the workplace.…”
Section: Discussionmentioning
confidence: 57%
“…Other scholars investigated the effectiveness of assertiveness training on nurses (Asi Karakas & Okanli, 2015 ; Kanade, 2018 ; Nakamura et al, 2017 ; Shimizu et al, 2004 ; Yoshinaga et al, 2018 ) and nursing students (Omura et al, 2019 ). Variables such as self-esteem (Binuja, 2020 ; Maheshwari & Gill, 2015 ; Shrestha, 2019 ) and psychological empowerment (Azizi et al, 2020 ; Bostanabad et al, 2018 ; Ibrahim, 2011 ) were found to be associated with assertiveness. However, for most studies, these variables were correlated with general assertiveness and not specifically with workplace assertiveness of nurses.…”
mentioning
confidence: 99%
“…The results of several studies were in line with the results of our study. For example, in a study, there has been a positive relationship between assertiveness and self‐esteem and a strong and inverse relationship between assertiveness and anxiety of nursing and midwifery students (Shrestha, 2019 ). The inverse relationship between assertiveness and anxiety has also been reported among nutritionists (Paterson et al., 2002 ).…”
Section: Discussionmentioning
confidence: 99%